2020
DOI: 10.2298/jsc190717098j
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer and antimicrobial properties of imidazolium based ionic liquids with salicylate anion

Abstract: Ionic liquids (ILs) are well known for their physicochemical properties that recommend them for many purposes. However, many ILs are not environmentally friendly. Bearing these facts in mind, a series of imidazoliumand salicylate-based ILs with low general toxicity were designed and their pharmacological potential studied. Herein, their antiproliferative effect against human cancer cell lines and antimicrobial activity on selected Gram-positive and Gram-negative bacteria and Candida strains are presented. ILs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 33 publications
1
2
1
Order By: Relevance
“…Additionally, one can note based on Wang et al results that the structure of the cation (ammonium, pyridinium, or imidazolium) with a similar number of -CH 2 - groups attached to nitrogen does not influence toxicity toward HeLa cells significantly, which is consistent with our previous observation for NHDF cell lines even if aliphatic quaternary ammonium ILs have been reported to be less hazardous in many other cytotoxicity studies . However, importantly, not only does the elongation of the alkyl chain length exert influence but also cation/anion functionalization may play a role, as clearly seen in the results presented by Jovanovic-Santa et al or Ferraz et al (see Table S1). Ferraz et al showed that ILs with hydroxyl-functionalized cations ([C 2 OHC 1 im] + ) are much more cytotoxic against HepG2 cells than ILs with nonfunctionalized cations ([C 2 C 1 im] + ).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Additionally, one can note based on Wang et al results that the structure of the cation (ammonium, pyridinium, or imidazolium) with a similar number of -CH 2 - groups attached to nitrogen does not influence toxicity toward HeLa cells significantly, which is consistent with our previous observation for NHDF cell lines even if aliphatic quaternary ammonium ILs have been reported to be less hazardous in many other cytotoxicity studies . However, importantly, not only does the elongation of the alkyl chain length exert influence but also cation/anion functionalization may play a role, as clearly seen in the results presented by Jovanovic-Santa et al or Ferraz et al (see Table S1). Ferraz et al showed that ILs with hydroxyl-functionalized cations ([C 2 OHC 1 im] + ) are much more cytotoxic against HepG2 cells than ILs with nonfunctionalized cations ([C 2 C 1 im] + ).…”
Section: Resultssupporting
confidence: 90%
“…These results stay in contrast with the conclusion presented in a very recently published review that polar substituents reduce toxicity . On the other hand, cytotoxicity data toward HeLa and A549 cell lines (see again Table S1) reported by Jovanovic-Santa et al are consistent with this rule. The results are different for each cell line.…”
Section: Resultscontrasting
confidence: 81%
“…The third generation of ILs is a fusion of physical, chemical, and biological properties and provides improved water solubility and permeability, low toxicity, and better bioavailability [ 12 , 14 ]. The promising anticancer properties of these agents toward malignant cell lines of several tumor models have already been described [ 12 , 17 , 43 , 44 , 45 , 46 ]. The combination of ILs with chemotherapeutic agents has also been studied, with promising results in terms of reducing chemotherapy toxicity [ 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ionic liquids (ILs) have been widely used in many fields due to their large variety and unique properties, which are a class of liquid compounds consisting of a bulky organic cation and relatively small anion and provided with excellent properties such as very low vapor pressure, nonvolatility, nonflammability, high thermal and electrochemical stability, and have been touted as greener alternatives to the conventional organic solvents [ 1 , 2 , 3 ]. However, the ILs create hazards to the natural environment and various biological levels of organization [ 4 , 5 , 6 ], which are indicated by the inhibition of enzymatic activity (e.g., acetylcholinesterase [ 7 , 8 , 9 ], the antioxidant enzyme of the animal liver [ 10 , 11 , 12 ]), the antimicrobial activity (e.g., Vibrio fischeri [ 13 ], Escherichia coli [ 14 , 15 ]), the phytotoxicity to aqueous and terrestrial plants [ 16 , 17 ] (e.g., Lemna minor [ 18 ], Ulva lactuca [ 19 ], Hordeum vulgare [ 20 , 21 ]), and the toxicity to invertebrates (e.g., Daphnia magna [ 13 , 22 , 23 ], Caenorhabditis elegans [ 24 ]) as well as vertebrates (e.g., Rana nigromaculata [ 25 ], Danio rerio [ 26 ], rat pheochromocytoma PC12 [ 27 , 28 ], even to human cell lines including human colon carcinoma CaCo-2 and HT-29 [ 29 ], IPC-81 [ 30 ], human cervical cancer HeLa [ 31 ], human lung carcinoma A549 [ 32 ], and so on. Furthermore, it was found that all the tested systems have shown distinctive susceptibilities by ILs at different levels.…”
Section: Introductionmentioning
confidence: 99%